2009
DOI: 10.1016/j.schres.2008.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Association of the 5′-upstream regulatory region of the α7 nicotinic acetylcholine receptor subunit gene (CHRNA7) with schizophrenia

Abstract: Background-The α7 neuronal nicotinic acetylcholine receptor subunit gene (CHRNA7) is localized in a chromosomal region (15q14) linked to schizophrenia in multiple independent studies. CHRNA7 was selected as the best candidate gene in the region for a well-documented endophenotype of schizophrenia, the P50 sensory processing deficit, by genetic linkage and biochemical studies.Methods-Subjects included Caucasian-Non Hispanic and African-American case-control subjects collected in Denver, and schizophrenic subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 70 publications
(79 reference statements)
4
77
0
Order By: Relevance
“…With respect to clinical considerations, a close association between nicotine addiction and schizophrenia has been found (Lohr & Flynn, 1992). Consistent with the hypothesis, that a gene-mediated dysfunction of α7 nAChR (Dome et al, 2010;Freedman et al, 1997;Stephens et al, 2009) underlies impairments seen in schizophrenia , the density of hippocampal [ 125 I]α-BGT binding sites was decreased in schizophrenic patients (Freedman et al, 1995) but was at control levels in schizophrenic smokers (Mexal et al, 2010). Evidence for an involvement of α7 nAChR in Alzheimer's disease (AD) was obtained at about 30 years ago from data showing a significantly reduced number of [ 125 I]α-BGT binding sites in the mid-temporal gyrus from demented patients (Davies & Feisullin, 1981).…”
Section: Alterations Of 7 Nachr In Diseased Brainsupporting
confidence: 71%
“…With respect to clinical considerations, a close association between nicotine addiction and schizophrenia has been found (Lohr & Flynn, 1992). Consistent with the hypothesis, that a gene-mediated dysfunction of α7 nAChR (Dome et al, 2010;Freedman et al, 1997;Stephens et al, 2009) underlies impairments seen in schizophrenia , the density of hippocampal [ 125 I]α-BGT binding sites was decreased in schizophrenic patients (Freedman et al, 1995) but was at control levels in schizophrenic smokers (Mexal et al, 2010). Evidence for an involvement of α7 nAChR in Alzheimer's disease (AD) was obtained at about 30 years ago from data showing a significantly reduced number of [ 125 I]α-BGT binding sites in the mid-temporal gyrus from demented patients (Davies & Feisullin, 1981).…”
Section: Alterations Of 7 Nachr In Diseased Brainsupporting
confidence: 71%
“…A significant association of SNP rs8028396 with smoking, as well as with smoking in schizophrenia, in a non-Hispanic Caucasian population was observed (Stephens et al, 2012;Neri et al, 2012). SNP rs3087454 was first shown to be significantly associated to schizophrenia (Stephens et al, 2009) and also influenced differences in synaptic activity, as detected by functional magnetic resonance imaging, between patients with schizophrenia and control subjects performing an auditory oddball task (Tregellas et al, 2010). A Korean population-based study on the development of either schizophrenia or bipolar disorder (BD) demonstrated that SNPs rs2337506, rs6494223, and rs12916879 exhibited only a marginal association with BD (Joo et al, 2010) and that SNP rs6494223 was associated with a protective effect in BD (Ancin et al, 2010) and impaired attention in patients with euthymic bipolar disorder (Ancin et al, 2011).…”
Section: A the Chrna7 Gene And Its Variantsmentioning
confidence: 99%
“…Subsequent analysis of smoking versus nonsmoking schizophrenics confirmed the reduced a7 nAChR expression at the cell surface but concluded that smoking might cause some compensation for this deficit (Leonard et al, 2000). Genetic studies conducted by different laboratories indicated that mutations in the CHRNA7 gene, its promotor region, or CHRFAM7A are associated with schizophrenia (Riley et al, 2000;Raux et al, 2002;Martin et al, 2007;Sinkus et al, 2009;Stephens et al, 2009;Bakanidze et al, 2013). A survey of the literature on schizophrenia and genetic association revealed that several studies failed to detect any association with CHRNA7 or CHRFAM7A, which is indicative of the rarity of these mutations in the schizophrenic population, the complexity of schizophrenia, and the need for a better classification of the disease (Petrovsky et al, 2009).…”
Section: B Schizophreniamentioning
confidence: 99%
“…It is located in the 15q13.3 critical region, and encodes the a7 subunit of the neuronal nicotinic acetylcholine receptor, a synaptic ion channel protein mediating neuronal signal transmission, widely expressed in the brain; both human and mouse model studies have provided evidences for association of the CHRNA7 gene with epilepsy and abnormal EEG, as well as with SCZ and its endophenotypes, and bipolar disorder. [19][20][21][22][23][24][25] A number of patients harbouring smaller microdeletions of an approximately 400-700 kb in size, which usually only include the CHRNA7 gene, have recently been reported in the literature; these atypical smaller rearrangements map to the distal region of the larger B1.5 Mb microdeletion and are mediated by NAHR between the CHRNA7-LCR and BP5. 4,11,[26][27][28] The range of clinical symptoms in the probands harbouring these smaller microdeletions is usually very similar to that observed in the subjects with the classical B1.5 Mb rearrangements, which suggests that the CHRNA7 gene may be responsible for the majority of the abnormal phenotypes associated with the 15q13.3 microdeletion syndrome.…”
Section: Mutational Spectrummentioning
confidence: 99%